Communication Gaps in Georgian Palliative Medicine: Ethical and Legal Review - Tebidze, N.; Kazhashvili, G. (European Scientific Journal, ESJ, 2024)
Introduction: Difficulties in communication, decision-making, and end-of-life management have emerged in the implementation of palliative care in recent decades. The imperfection of ethical issues was also highlighted. This fact is confirmed once again by a study conducted by the oncology department of the Batumi High-technology Hospital, which aimed to study the adequate perception of existing oral pathologies by patients under palliative care and their impact on the quality of life. Aim: We aimed to discuss the mentioned problem within the framework of bioethics and Georgian legislation. Methods: Despite the few amount of literary sources, we tried to discuss the mentioned issue based on Georgian legislation and also existing literature. Conclusion: Thus, as we mention in medical activities there are cases when the real diagnosis is not told to the patient for , his favor’’, also there are cases when an inappropriate diagnosis is made, which can lead the patient to a fatal condition. In this case, the patient can civilly protect his rights. The best option is to provide the patient with information in the correct form so that it does not mean the end of the world and does not cause depression in him. The patient should be able to pass the last stage of life peacefully and with dignity.